Maternal diet modulates placental nutrient transporter gene expression in a mouse model of diabetic pregnancy - Kappen, Claudia; Kruger, Claudia; Jones, Sydney; Herion, Nils Janis; Salbaum, J. Michael (PLOS ONE, 2019)
Diabetes in the mother during pregnancy is a risk factor for birth defects and perinatal complications and can affect long-term health of the offspring through developmental programming of susceptibility to metabolic disease. We previously showed that Streptozotocin-induced maternal diabetes in mice is associated with altered cell differentiation and with smaller size of the placenta. Placental size and fetal size were affected by maternal diet in this model, and maternal diet also modulated the risk for neural tube defects. In the present study, we sought to determine the extent to which these effects might be mediated through altered expression of nutrient transporters, specifically glucose and fatty acid transporters in the placenta. Our results demonstrate that expression of several transporters is modulated by both maternal diet and maternal diabetes. Diet was revealed as the more prominent determinant of nutrient transporter expression levels, even in pregnancies with uncontrolled diabetes, consistent with the role of diet in placental and fetal growth. Notably, the largest changes in nutrient transporter expression levels were detected around midgestation time points when the placenta is being formed. These findings place the critical time period for susceptibility to diet exposures earlier than previously appreciated, implying that mechanisms underlying developmental programming can act on placenta formation.
Gesehen am 23.03.2021